Midgut malrotation: case series - Gupta, Dimple; Paruthy, Shivani B.; Das, Anirban; Thakur, Radhika (International Surgery Journal, 2021)
Mal rotation of midgut is associated with other anomalies usually encountered in neonatal period or early childhood. If undetected in childhood it presents in adulthood with small bowel obstruction, repeated appendicitis or chronic abdominal symptoms. CECT abdomen is mandatory for diagnosis though it often presents as surgical surprise on abdominal laparotomy. Hereby, we presented 3 cases where it was undetected till adulthood though CECT was mandatory for definitive diagnosis. Case 1 patient presented with chronic abdominal pain on left abdomen was actually malrotation with appendix lying on left hypochondrium and stenosed fourth part duodenum adding to vomiting off and on. Case 2 patient in adulthood presented with repeated sub-acute intestinal obstruction because of midgut mal-rotation. Relieved after Ladd band was cut and obstructive symptoms relieved. Case 3 patient had inflammed appendix in subhepatic position was cause of chronic pain with para duodenal hernial sac adding to intestinal obstruction with malrotation of midgut.